Terrorism and Political Self-Placement in European Union Countries - Athina Economou; Christos Kollias (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Terrorism is widely regarded as a public bad vis-à-vis security - a public good - affecting the subjective well-being of citizens. As studies have shown, citizens' risk-perceptions and risk-assessment are affected by large scale terrorist acts. Reported evidence shows that individuals are often willing to trade-off civil liberties for enhanced security particularly as a post-terrorist attack reaction as well as adopting more conservative views. Within this strand of the literature, this paper examines whether terrorism and in particular mass-casualty terrorist attacks affect citizens' political selfplacement on the left-right scale of the political spectrum. To this effect the Eurobarometer Surveys for twelve European Union countries are utilised and Ordered Probit models are employed for the period 1985-2010 with over 230 thousand observations used in the estimations. On balance, the findings reported herein seem to be pointing to a shift in respondents' self-positioning towards the right of the political spectrum.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330